The Stress Barometer: Validation of a Bio–Psycho–Social Brief Screening Instrument of Pandemic Stress Reaction - Eckhard, Alina; Menne, Britta; Salzburger, Mareike; Poppelreuter, Martin; Bering, Robert (Frontiers in Psychology, 2022)
Background: To capture the psychosocial impact of the SARS-CoV-2 pandemic, a model based on the International Classification of Functioning, Disability and Health (ICF) was developed during the first lockdown in Germany in April 2020. FACT-19, the questionnaire for the assessment of pandemic stress load, measures 1) pre-pandemic stress, 2) pandemic stress and 3) contextual factors (functioning as facilitators or barriers). Derived from this model, the stress barometer as a brief screening instrument captures these factors as a short version. Method: For validation purposes, the stress barometer was applied in conjunction with the Symptom-Checklist SCL-90-S at the beginning of the first lockdown in psychosomatic and psychotraumatological care in two federal states in Germany. Results: The structure of the short screening was examined in the overall sample (n = 341) using an exploratory factor analysis (Chi² (78) = 875.720, KMO = .688). The results indicate a four-factor-structure that explains 59,5% of the total cumulative variance. The factors of the stress barometer correlate with the Global Severity Index (GSI, measured by SCL-90-S) with moderate to weak effects: pre-pandemic stress (rs = .431, p <.001, n = 295), pandemic stress (rs = .310, p <.001, n = 298), external facilitator (rs = -.155, p <.001, n = 312) and internal barriers (rs = .232, p <.001, n = 312). Discussion: The results indicate the suitability of the stress barometer to complement the measurement of the impact of pandemics with an ICF-oriented approach, taking into consideration pre-pandemic stress and interactions with facilitators and barriers.